DARURAT MORAL DAN SOLUSI NARATIF: ANALISIS DESKRIPTIF 'BRIANNA DAN BOTTOMWISE' DALAM UPAYA MEMBANGUN KARAKTER BANGSA MELALUI SASTRA - Syafi Junadi; Ali Manshur; Moh. Syamsul Ma’arif (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
The purpose of this study is to describe the form of use of character education values ??of the main characters in the novel Brianna and Bottomwise by Andrea Hirata. This research method uses a qualitative approach with a descriptive qualitative research type. The data source used in this study comes from the novel Brianna and Bottomwise by Andrea Hirata, namely the character education values ??of the main characters in the novel. The researcher's data collection procedure uses the Simak Catat technique. The findings of this study indicate that the form of character education values ??in the novel Brianna and Bottomwise by Andrea Hirata contains eight values ??found in the characters of the main characters. These character education values ??are honesty, gratitude, hard work or perseverance, wisdom, courage, independence, optimism and caring.